Subcultural Masculine Moral Identity Work among Rural Missouri Noodlers: "A Special Breed of Men" - Grigsby, Mary (Anthropologica, 2022)
This paper analyzes how male Missouri "noodlers" (hand fishers) account for the persistence of illegal catfish catch- ing across generations. Noodling is central to the way men con- struct a subculturally worthy identity based on trust, respect, sharing, reciprocity and recognition of interdependence with members of their group, community and the local natural envi- ronment. The noodling subculture rejects the definition of noodling as poaching and constructs a group definition of noodling as a worthy masculine community-building tradition.